2008
DOI: 10.1590/s0100-06832008000200013
|View full text |Cite
|
Sign up to set email alerts
|

Nodulação e produção do caupi (Vigna unguiculata L. Walp) sob efeito de plantas de cobertura e inoculação

Abstract: RESUMOUm experimento de campo foi realizado no município de Crato -Ceará para estudar como a planta de cobertura afeta a nodulação e produtividade de caupi (Vigna unguiculata (L.) Walp), submetido a diferentes inoculações. Empregou-se o delineamento em blocos casualizados, no esquema em parcelas subsubdivididas, com quatro repetições. Os tratamentos consistiram de plantas de cobertura, formando a parcela principal; inoculação, como subparcela; e amostragens quinzenais, como subsubparcela. As plantas de cobertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(10 reference statements)
0
3
0
3
Order By: Relevance
“…Os resultados encontrados no presente trabalho corroboram aos encontrados por Nascimento et al (2008Nascimento et al ( , 2010 e Zilli et al (2009), avaliando o desenvolvimento e a produtividade do feijão-caupi em condições de campo, onde a inoculação com estirpes recomendadas permitiram produção de biomassa e grãos no feijão-caupi semelhantes à da adubação com 50 kg ha -1 de N.…”
Section: Methodsunclassified
“…Os resultados encontrados no presente trabalho corroboram aos encontrados por Nascimento et al (2008Nascimento et al ( , 2010 e Zilli et al (2009), avaliando o desenvolvimento e a produtividade do feijão-caupi em condições de campo, onde a inoculação com estirpes recomendadas permitiram produção de biomassa e grãos no feijão-caupi semelhantes à da adubação com 50 kg ha -1 de N.…”
Section: Methodsunclassified
“…Melo and Zilli (2009) showed that the interference of soil and climate factors reduced the nodulation of V. unguiculata plants grown in the field compared to those grown in a greenhouse. The success in nodulation of leguminous plants is a complex process that depends on different environmental factors, such as amount of available P (Abbasi et al, 2008), presence of other leguminous plants nearby (Nascimento et al, 2008), soil acidity (Meghvansi et al, 2005), interaction with microorganisms (Azcón-Aguilar and Barea, 2015), and water and heat stresses (Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Melo and Zilli (2009) showed that the interference of soil and climate factors reduced the nodulation of V. unguiculata plants grown in the field compared to those grown in a greenhouse. The success in nodulation of leguminous plants is a complex process that depends on different environmental factors, such as amount of available P (Abbasi et al, 2008), presence of other leguminous plants nearby (Nascimento et al, 2008), soil acidity (Meghvansi et al, 2005), interaction with microorganisms (Azcón-Aguilar and Barea, 2015), and water and heat stresses (Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%